PUTUSAN PRAPERADILAN YANG MENYIMPANG SECARA FUNDAMENTAL - AMIR GIRI MURYAWAN (Jurnal Penegakan Hukum Indonesia, 2021)
Pretrial hearing is designed for a simple issue, no more than to control administrative proceedings of criminal enforcement. This can be seen from the simplicity of the pretrial hearing concept in Article 77 of the Criminal Procedure Code. Demands for justice for suspects/defendant led to developments in the pretrial system. However, these developments have a negative side, resulting in idealized norms being modified in such a way as to meet sociological interests, which are not necessarily in line with their philosophical and juridical aspects. The most visible impact is that the Judicial Review against Article 77 of the Criminal Procedure Code results in broading the object of pretrial hearing that has serious implications for the procedure law. The problem in this research is whether the decision of pretrial in assessing the core issue of the case includes "pretrial decisions that are considered fundamentally deviant"? This type of legal research is a normative with a prescriptive nature that re-testing vague of norms against legal theory. The results of the research are the decision of pretrial hearings that assess the core issue of the case is fundamentally deviant, because pretrial hearing only have the authority to "examine" and "decide" meaning that they can only move within the scope / realm of administration only. It is different when a judge is given the authority to "adjudicate", then the court will be allowed to examine the subject matter of the case.